Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1002/ijc.24322
|View full text |Cite
|
Sign up to set email alerts
|

Molecular variants of HPV‐16 associated with cervical cancer in Indian population

Abstract: Human papilloma virus is a causative factor in the etiology of cervical cancer with HPV16 being the most prevalent genotype associated with it. Intratype variations in oncogenic E6/E7 and capsid L1 proteins of HPV 16 besides being of phylogenetic importance, are associated with risk of viral persistence and progression. The objective of this multicentric study was to identify HPV-16 E6, E7 and L1 variants prevalent in India and their possible biological effects. Squamous cell cervical cancer biopsies were coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
32
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 49 publications
7
32
3
Order By: Relevance
“…The E7 variant A647G leading to a change from Asn to Ser at amino acid position 29 has been reported by Ding et al 18 However, this change should alter the functions of E7 protein including cell immortalization, activation of cyclins E and A, inhibition of cyclin dependent kinase inhibitors, enhancement of foreign DNA integration and mutagenecity. 19 Unlike that has been reported to be absent in India by Pande et al, 20 this variant was identified in 42.9% (61/142) of our samples. In a Korean study, 21 the E-prototype was detected in only 10% of patients of invasive cervical carcinomas, whereas the variant N29S was present in 70% of invasive cervical carcinomas.…”
Section: Discussioncontrasting
confidence: 73%
“…The E7 variant A647G leading to a change from Asn to Ser at amino acid position 29 has been reported by Ding et al 18 However, this change should alter the functions of E7 protein including cell immortalization, activation of cyclins E and A, inhibition of cyclin dependent kinase inhibitors, enhancement of foreign DNA integration and mutagenecity. 19 Unlike that has been reported to be absent in India by Pande et al, 20 this variant was identified in 42.9% (61/142) of our samples. In a Korean study, 21 the E-prototype was detected in only 10% of patients of invasive cervical carcinomas, whereas the variant N29S was present in 70% of invasive cervical carcinomas.…”
Section: Discussioncontrasting
confidence: 73%
“…Previous studies have shown that some nucleotide substitutions have remarkable importance in pathogenicity [11,20,21,22]. In the present study, 16 nucleotide variations were detected.…”
Section: Discussionsupporting
confidence: 56%
“…Multiple-variant infections, which have been rarely described in the literature [16][17][18] , have epidemiological and diagnostic relevance. Some HPV intratype variants have been associated with geographic specificity and worldwide migration of the human host 19,20 , increased oncogenicity 21,22 , and might be responsible for escape to prophylactic vaccination 23 .…”
Section: Discussionmentioning
confidence: 99%